"Extreme Confusion and Disorder"? The Japanese Economy in the Great Kantō Earthquake of 1923. Issue 3 (16th September 2014) - Hunter, Janet
<x content-type="archive" xml:space="preserve">Abstract</x> Contemporary concerns about the difficulties faced by the Japanese economy following the Great Kantō Earthquake of 1923 soon appeared to be unfounded as the economy recovered relatively quickly. This paper suggests that despite its limited impact on Japan's longer-term economic trajectory this disaster can tell us a great deal about the ways in which individuals, organizations, and officialdom respond to a devastating event, and help us better understand the process of transition from immediate relief to longer-term recovery, not just in Japan, but more broadly. It analyzes the impact of the disaster on market transactions, showing that the scale and nature of market disruption went far beyond direct physical destruction; that the collective and individual responses of government, producers, traders, and consumers had the potential to make matters worse, rather than better; and that the existence of integrated markets spread the effects of the disaster across the Japanese archipelago. It also suggests that reestablishing market stability following the crisis was one of the keys to longer-term recovery, and that further research will help us understand the causal factors in that process.